EFEK PENGUMUMAN KEBIJAKAN DIVIDEN TERHADAP RETURN SAHAM YANG TERGOLONG JAKARTA ISLAMIC INDEXS - Endri Endri (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
This research aims to test dividend signaling theory in the Jakarta Islamic Index groups. Signaling theory states that dividend policy has information content that can influence to share price. This research usesamples in the form of company allocating dividend for period 2006-2007 which listed on Jakarta Islamic Index. Final samples which are utilized in this research are equal to 12 firms observation. Using the event-study method, the result of our research shows that at the significant level of 5%, there is only one working days which yield the abnormal return that is significant at the dividend announcements. Those are the sixth day before the event date with the value of 0.00889 or around 0.9%. The final conclusion is that stock price will negatively reacted to the announcement of dividend. Overall, the evidence tends to support the dividend irrelevancy hypothesis, but does not provide a support for the signaling theory. Evidence also indicates that dividend payment does not signal any information to the investors, which needs to be further investigated.